2017
DOI: 10.1007/s13595-016-0607-9
|View full text |Cite
|
Sign up to set email alerts
|

Determining the appropriate timing of the next forest inventory: incorporating forest owner risk preferences and the uncertainty of forest data quality

Abstract: & Key message The timing to conduct new forest inventories should be based on the requirements of the decision maker. Importance should be placed on the objectives of the decision maker and his/her risk preferences related to those objectives. & Context The appropriate use of pertinent and available information is paramount in any decision-making process. Within forestry, a new forest inventory is typically conducted prior to creating a forest management plan. The acquisition of new forest inventory data is ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The mechanism by which the interest rate affected the results was via different management intensity applied to stands with different structures. In other studies, the interest rate has been found to affect the optimal data accuracy (Kangas et al 2015) depending on risk aversion of a decision-maker (Eyvindson et al 2017). Because of interactions between inventory data and external factors that constrain the feasible set of management actions, it is recommended not to separate but to integrate the inventory and planning systems for well-informed decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which the interest rate affected the results was via different management intensity applied to stands with different structures. In other studies, the interest rate has been found to affect the optimal data accuracy (Kangas et al 2015) depending on risk aversion of a decision-maker (Eyvindson et al 2017). Because of interactions between inventory data and external factors that constrain the feasible set of management actions, it is recommended not to separate but to integrate the inventory and planning systems for well-informed decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, according to a metaanalysis of five studies (Kangas et al 2018a), a unit increase in the relative root mean squared error of total volume increased losses due to suboptimal decisions by 4.4 €/ha, on average. Factors affecting optimal quality of inventory data have further been addressed by Mäkinen et al (2012), Kangas et al (2015), Eyvindson et al (2017), and Ruotsalainen et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The economic losses denote how much more utility the forest owner could get by rescheduling the cuttings and other forest management operations. Regarding the forest owner, a new inventory or supplementing one can be worth it if new incomes from the forestry are greater than the increased inventory costs (Eyvindson et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Related to the issue of DA, the specific timing of when the data should be updated can be formulated as a multistage stochastic optimization problem. Based on the preferences of the decision maker and the optimization model used, the improvement of forest information could be timed specifically (Eyvindson et al 2017).…”
Section: The Potential For Using Da In Forest Planningmentioning
confidence: 99%